Impact Of Reduced Tillage On The Preservation of Soil Fertility And Macrofauna In Semi-Arid Conditions - Issaoun Djamila; Metahri Mohammed Said; Annabi Mohamed; Setbel Samira (Ekológia (Bratislava))
Cereals and pulses are an important part of agricultural production in Algeria, particularly in semi-arid regions that are affected and influenced by climatic, geographic, and agronomic factors. Maintaining a reliable and sustainable agricultural production system has become one of the primary concerns of arid and semi-arid producers. Conservation agriculture is recommended by researchers as an effective technique for limiting soil degradation, preserving soil fertility and biodiversity, and ensuring long-term agricultural production, while protecting natural resources and the environment. This study is part of a Technical Institute of Field Crops (ITGC) project in Sétif that aims to assess the effect of conventional tillage (CT) and no tillage (NT) on the chemical and biological quality of Sétif›s soils. The pH of these soils ranged from 7.34 to 7.83, indicating that they were moderately basic to alkaline. An analysis of variance revealed that tillage type had no effect on pH, whereas crop type and depth had a significant effect. According to the findings, NT improves organic matter levels compared to CT. The fauna inventory uncovered a total of 2089 individuals representing 14 different species. There were 1329 individuals in the NT subplot. This number is higher than the 760 individuals recorded in the conventionally seeded subplot. Shannon–Weaver had a high diversity index value. More efforts are required to promote conservation agriculture in these areas.